ANALISIS PENGELOLAAN MODAL KERJA DALAM MENINGKATKAN LIKUIDITAS DAN PROFITABILITAS PADA PT. PERKEBUNAN NUSANTARA V PEKANBARU - Tanjung, Abdurrahman; Ibrahim, Mariaty (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2021)
Good working capital management determines the effectiveness and efficiency of the activities carried out by the company. This study aims to determine and analyse the effectiveness of working capital management in increasing liquidity and profitability at PT. Perkebunan Nusantara V Pekanbaru. The type of data used in this study is descriptive quantitative data. The data source uses primary data obtained through interviews and secondary data using the financial statements of PT. Perkebunan Nusantara V Pekanbaru Tbk for the period 2015-2019 and using ratio analysis. The results of the study are as follows: First, the management of working capital to liquidity causes a decrease in the current ratio, but sometimes increases. The decrease in current ratio was due to a significant increase in current assets compared to the previous year. Second, the management of working to profitability causes a decrease in return on investment. But sometimes increases. Return on investment and return on equity which is caused by the company's net profit has decreased significantly compared to the previous year. Keywords: working capital, liquidity and profitability.